FGF18 Inhibits Clear Cell Renal Cell Carcinoma Proliferation and Invasion via Regulating Epithelial-Mesenchymal Transition - Yang, Chen; Zhang, Zheyu; Ye, Fangdie; Mou, Zezhong; Chen, Xinan; Ou, Yuxi; Xu, Chenyang; Wu, Siqi; Cheng, Zhang; Hu, Jimeng; Zou, Lujia; Jiang, Haowen (Frontiers in Oncology, 2020)
Fibroblast growth factor 18 (FGF18) is a member of the FGF family and contributes to a broad range of biological events. The important role of the overexpression of FGF18 has been identified in the progression of several types of cancers. However, there is still little information on the biological role of FGF18 on clear cell renal cell carcinoma (ccRCC), which is of interest in investigating the biological functions of FGF18 in ccRCC. Our results showed that FGF18 was lowly expressed in ccRCC tissues compared to paired normal renal tissue from the TCGA database and clinical cohort of Huashan Hospital and that high expression of FGF18 correlated with a good prognosis in ccRCC patients. In addition, overexpression of FGF18 significantly inhibited the proliferation ability of ccRCC cell lines in vitro and in vivo. Gene set enrichment analysis (GSEA) identified epithelial-mesenchymal transition (EMT) involved in a high FGF18 expression group of ccRCC patients in the TCGA cohort, which was further validated with EMT related markers in FGF18 overexpressed ccRCC cell lines. Furthermore, FGF18 overexpression significantly inhibited the PI3K/Akt pathway in ccRCC cells. Taken together, this study concludes that FGF18 is of potential value as a target for ccRCC.